Exploring non-pressure methods for plywood protection: efficacy of tannin and copper chromium boron (CCB) in fungal resistance and flame retardancy - Bednarczuk, Ezaquel; Hillig, Éverton; Júnior, Eraldo Bonfatti [UNESP]; Ferro, Fabiane Salles; Miranda, Gabriel Magalhaes (Taylor & Francis, 2025)
This study evaluated tannins and copper chromium boron (CCB) as preservatives and flame retardants, respectively, for the treatment of wood veneers using non-pressure methods. The plywood panels were manufactured using Pinus taeda and Eucalyptus dunnii veneers. CCB showed good efficacy against fungal decay, whereas tannins, investigated as natural and environmentally friendly alternatives, offered benefits for sustainable wood protection strategies. After preservative application, panels were manufactured using phenol-formaldehyde adhesive and subjected to accelerated biodegradation tests with Trametes versicolor and Gloeophyllum trabeum, as well as a burn test. The non-pressure processes achieved reasonable penetration and retention of the preservatives in the veneers, which was accompanied by color alterations confirmed through colorimetric analysis. The panels treated with CCB showed high biological resistance and were classified as “very resistant.” Tannin-treated panels exhibited only partial protection against brown rot fungus, resulting in a “resistant” classification. In the burn test, neither CCB nor tannin improved fire resistance, with the concentration and application methods insufficient to produce a relevant flame-retardant effect. Tannin has potential as an alternative, but advances in formulation and application are required to replace conventional preservatives.